A study on utilization of Janani Suraksha Yojana and its association with institutional delivery in the state of West Bengal, India - Dipta K Mukhopadhyay; Sujishnu Mukhopadhyay; Sarmila Mallik; Susmita Nayak; Asit Kumar Biswas; Akhil Bandhu Biswas (Wolters Kluwer Medknow Publications, 2016)
Background: India launched the Janani Suraksha Yojana (JSY) on the principles of conditional cash transfer providing monetary incentive to needy women to improve access to institutional childbirth. Objectives: This study was conducted among JSY-eligible women who delivered between April 2012 and June 2012 to assess the utilization of cash incentives toward institutional delivery, along with other associated factors influencing institutional delivery. Methods: It was a cross-sectional, descriptive study conducted between July 2012 and May 2013 on 946 women selected through stratified random sampling of subcentres from better and worse performing districts of West Bengal. Results: 74.7% of the study population was JSY-eligible. 90.2% of those who took three antenatal check-ups (ANCs) and 36.8% JSY-noneligible women received cash. Government institutions were preferred for childbirth among all groups irrespective of JSY eligibility, receipt of cash, and number of antenatal visits. Overall, 78.8% opted for institutional delivery if they had received cash, which was significantly more than those who did not (64.5%). JSY-eligible women were 1.5 times more likely to deliver in government institutions compared to JSY-noneligible women. With no incentive, the likelihood of institutional delivery was halved. The distance of a 24 Χ 7 delivery hub beyond 5 km (74.8% vs. 81.8%), the religion of Islam (62.7% vs. 83.2%), and multiparity (63.9% vs. 83.6%) were significant deterring factors. Conclusion: Despite some inclusion and exclusion errors, cash incentive under JSY was associated with increased institutional delivery, especially in government institutions though there were other factors influencing the decision as well.